Discrete Benzotriazole‐Copper(II) Complexes in Chelated and Non‐Chelated Coordination Modes: Structural Analysis and Catalytic Application in Click and A3 Coupling Reactions. Issue 18 (27th April 2021) - Pandey, Sharmila; Mandal, Tanmoy
Abstract: Two copper(II) complexes with benzotriazole‐based ligands having pyridyl and quinolinyl arms were synthesized in good yields and characterized fully via spectroscopic and crystallographic techniques. The crystal structures of the complexes revealed different coordination environments around copper(II) centers. The difference in structure was due to the steric effect of the ligands, which resulted in an octahedral and a square pyramidal geometry of the resulting complexes in the solid state. Both the air‐stable complexes were utilized as precatalysts in catalytic click reactions and A 3 coupling. Abstract : Two discrete Cu(II) complexes, [Cu(BTZ‐2P)2 (ClO4 )2 ] and [Cu(BTZ‐2Q)2 (CH3 CN)2 (H2 O)](ClO4 )2 (BTZ‐2P =1‐(pyridine‐2‐yl)‐1H‐benzo[ d ][1, 2, 3]triazole; BTZ‐2Q =1‐(quinoline‐2‐yl)‐1H‐benzo[ d ][1, 2, 3]triazole), with variable coordination modes and structural features, were accessed with pyridine and quinoline‐appended benzotriazoles, and they were applied as effective precatalysts in click and A 3 coupling reactions.